`Should I Stay or Should I Go?' - A Case Study on Young Women Leaving Rural Sweden - Daniel Rauhut; Mats Johansson (European Regional Science Association (ERSA), 2012)
Labour market structures which offer fewer options to women than to men and relatively poor educational facilities are usually mentioned as main reasons why remote and economically weak regions are affected by selective out-migration and shortage of young women. Also traditional gender structures and "macho" lifestyles are often heard motives that influence the out-migration of young women from rural areas. This sex-biased out-migration has been ongoing for more than 40 years for some rural regions in Sweden. This paper is a spin-off product from the ESPON-project SEMIGRA – Selective Migration and Unbalanced Sex Ratio in Rural Regions – and aims to analyse the out-migration of young women from the rural Swedish region Västernorrland. The theoretical frameworks are based upon the neoclassical macro theory of migration and the dual labour market theory in combination with the human capital theory. A qualitative method will be used in the analysis in this study. The empirical material consists of a literature review, a survey to 5,512 teenagers aged 14-17, expert interviews and interviews with young women leaving Västernorrland, returning to Västernorrland or moving in without any prior connection to the region. The driving forces of out-migration of young women appear connected to studies and moving to more female-friendly labour markets. In the household creating ages the findings suggest a return-migration flow with net in-migration as one result: Västernorrland is considered a safe and good place for the children to grow up in. Being close to the grandparents is highly valued, while a consumption-based metropolitan life-style appears less important for the interviewed women. For those who do not return the lack of employment possibilities in their profession appears to be the main reason for not returning. Furthermore, the findings suggest that the young adults, and especially young women, are rational in their decision to move from Västernorrland due to better opportunities to get a job and education. With regard to out-migration, the findings also suggest that young people with an immigrant background experience push-factors natives do not experience: the survey as well as the expert interviews and interviews with young women indicate racism or discrimination based upon ethnicity.
Keywords: 330